PENENTUAN KONDISI OPTIMUM FERMENTASI PADAT Trichoderma hamatum PADA MEDIA TUMBUH DEDAK PADI DALAM PRODUKSI SELULASE MENGGUNAKAN RESPONSE SURFACE METHODOLOGY - Teuku Beuna Bardant; Haznan Abimanyu; Putri Lili Epriyani (Research Center for Chemistry - LIPI, 2013)
Optimum condition for solidfermentation of Trichoderma hamatum inrice bran in order to produce cellulase hadbeen studied by using Response Surfacemethodology (RSM). Fermentationcondition variables that observed waswater to rice bran ratio, urea andinoculums additions cellulase activity inFPU/gds (gram of dry solid) became theonly dependent variable. The result ofempirical equation from this study wasproven to be valid within water to ricebran ratio 0,5 - 0,7, urea and inoculumsaddition where 2-3 % and 1-2% of ricebran weight respactively. Maximumcellulase activity that can be obtain withinthese ranges was 4.99 Â± 0.92 FPU/gds.Keywords: Cellulase, Trichodermahamatum, rice bran, solid fermentation